2013
DOI: 10.1080/14733285.2013.812304
|View full text |Cite
|
Sign up to set email alerts
|

Children's daily travel to school in Johannesburg-Soweto, South Africa: geography and school choice in the Birth to Twenty cohort study

Abstract: This paper has two aims: to explore approaches to the measurement of children's daily travel to school in a context of limited geospatial data availability and to provide data regarding school choice and distance travelled to school in Soweto-Johannesburg, South Africa. The paper makes use of data from the Birth to Twenty cohort study (n ¼ 1428) to explore three different approaches to estimating school choice and travel to school. First, straight-line distance between home and school is calculated. Second, ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(12 citation statements)
references
References 39 publications
0
8
0
4
Order By: Relevance
“…The schools included in the current study were located in suburban, middle-class neighborhoods, which predominantly served White adolescents before 1994 but which are now racially integrated. These schools are also considered to be functioning better than schools in less advantaged areas (Spaull, 2015) and are often attended by learners from the latter areas (de Kadt, Norris, Fleisch, Richter, & Alvanides, 2014). It is possible that Black adolescents are more satisfied with school because of perceiving it as better than alternative options previously accessible to them.…”
Section: Discussionmentioning
confidence: 99%
“…The schools included in the current study were located in suburban, middle-class neighborhoods, which predominantly served White adolescents before 1994 but which are now racially integrated. These schools are also considered to be functioning better than schools in less advantaged areas (Spaull, 2015) and are often attended by learners from the latter areas (de Kadt, Norris, Fleisch, Richter, & Alvanides, 2014). It is possible that Black adolescents are more satisfied with school because of perceiving it as better than alternative options previously accessible to them.…”
Section: Discussionmentioning
confidence: 99%
“…Some of the most wide‐ranging work (but of less direct relevance here), is the longstanding use of “cohort studies” across a range of disciplines in a methodological sense. Cohort studies afford often quantitative, longitudinal, large‐scale, demographic studies of particular birth cohorts, in order to assess synchronous and diachronous similarities and differences in health, attitudes, mobilities, and far more besides (for recent geographical examples, see de Kadt et al., ; Camara & Garcia‐Roman, ).…”
Section: Theorising Cohortness and (Student) Identitiesmentioning
confidence: 99%
“…Evidence for this traveling comes from a number of sources. One Soweto-Johannesburg quantitative study found that only 18% of learners attend their nearest school (De Kadt et al, 2014). Qualitative studies in Cape Town (Fataar, 2010), Johannesburg (Bell and McKay, 2011), and Durban (Hunter, 2010) found high levels of school children traveling.…”
Section: The Politics Of Schooling Choice In South Africamentioning
confidence: 97%